Mise Au Point D’un Protocole De Sterilisation D’explants Nodaux D’alchornea Cordifolia Avec De L’acide Triclororoisocyanurique - Mokea-Niaty, Aurélien; Mve, Samson Daudet Medza; Lepengue, Alexis Nicaise; Beyeme, Antoine Mitte Mbeang; Moupela, Christian; Ognalaga, Maurice; Eko, Darlène Badjina; Mustafa, Nabil Sabet; M’batchi, Bertrand (European Scientific Journal, ESJ, 2017)
Trichloroisocyanuric acid is a swimming pool disinfectant and is readily accessible. As a result, there is the need to use it as a substitute for conventional disinfectants in in vitro culture. Nodal explants of Alchornea cordifolia, harvested in a natural environment, have been rinsed abundantly with Dettol under running water. Then it was soaked in Talo Plus (550 g/l carbendazim and 100 g/l Chlorothalonil) at 5 ml/liter, which is a broad spectrum fungicide. After then, it was immersed in 70% alcohol for 10 minutes before being soaked in different solutions of trichloroisocyanuric acid to: 6, 4, 3, 2, 1, 0.3, 0.1, and 0.08%. The explants were disinfected completely of all contaminating bacterial and fungal exogenous. This was after a treatment in solutions of acidic trichloroisocyanurique of 6 to 0.08%. The results showed that the losses of active chlorine remained low during storage at temperatures of 4 to 18 ± 2°C. They reach only 5.29% after 72 hours. At room temperature of 27 ± 2 ° C, these losses are more than 30% after three days. Concentrations of 0.1 to 0.3% are effective for the disinfection of explants. This protocol of explants disinfection in vitro culture could therefore be advantageously substituted using the hypochlorite of calcium or the chloride of mercury.